2012
DOI: 10.1021/jf302451c
|View full text |Cite
|
Sign up to set email alerts
|

Malondialdehyde Measurement in Oxidized Foods: Evaluation of the Spectrophotometric Thiobarbituric Acid Reactive Substances (TBARS) Test in Various Foods

Abstract: The ability of the spectrophotometric thiobarbituric acid reactive substances (TBARS) test to determine malondialdehyde (MDA) in various food matrices was evaluated. MDA was extracted from the foods; the extract reacted with thiobarbituric acid (TBA); and the formed TBA-MDA adduct was measured spectrophotometricaly at 532 nm. In parallel, the TBA-MDA adduct was analyzed with high-performance liquid chromatography (HPLC) coupled with fluorescence detection. Oils and unprocessed and uncooked meat and fish produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
139
3
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 256 publications
(158 citation statements)
references
References 33 publications
(58 reference statements)
3
139
3
6
Order By: Relevance
“…The findings of the current study are in close agreement with the results of other studies [14,15]. Several studies have demonstrated the beneficial effects of B.vulgaris on oxidative stress parameters in diabetic rats, which are consistent with our results [6,16]. In diabetes, the pancreas is considered to be the principal target organ susceptible to oxidative stress and damage produced by free radicals.…”
Section: Discussionsupporting
confidence: 93%
“…The findings of the current study are in close agreement with the results of other studies [14,15]. Several studies have demonstrated the beneficial effects of B.vulgaris on oxidative stress parameters in diabetic rats, which are consistent with our results [6,16]. In diabetes, the pancreas is considered to be the principal target organ susceptible to oxidative stress and damage produced by free radicals.…”
Section: Discussionsupporting
confidence: 93%
“…28 Thiobarbituric acid reactive substances assay was used to detect and quantify any MDAs formed. 33,34 It is a common method to measure oxidative change in lipids due to free radicals. 35 It was found that there was a continuous increase in the MDA formation in each hour (Figure 7).…”
Section: Mda Quantificationmentioning
confidence: 99%
“…TBARS determination was performed according to Papastergiadis et al [28]. The fermentation supernatants were centrifuged for 15 min at 3000 g and filtered through a 150-mm filter paper.…”
Section: Extraction and Determination Of Thiobarbituric Acid-reactivementioning
confidence: 99%